Application of Innovative Practices by Business Educators for Improving Societal Values in South-East Nigeria - Justina I. Ezenwafor; Eunice Ihejirika (International Journal of Education, Teaching, and Social Sciences, 2022)
The increasing level of moral decadence among the people of South-East Nigeria necessitated the study to determine innovative practices being applied by business educators to improve societal values in the area. Two research questions guided the study and four null hypotheses were tested. Descriptive survey research design was adopted for the study. The entire population of 215 business educators in all public tertiary institutions in the area was studied without sampling as the researchers were able to manage the size. A validated Likert scale questionnaire containing 24 items in two clusters was used for data collection. The instrument was tested for reliability and an overall reliability coefficient value of 0.76 was obtained. Data collected were analyzed using the arithmetic mean to answer the research questions and standard deviation to determine how homogenous the respondents were in their views. ANOVA was used to test the null hypotheses at 0.05 level of significance. Findings revealed that the subjects apply the two innovative practices in the study at a great extent. The respondents differed significantly in their extent of application of social responsibility principles as a result of educational attainment and experience but did not in ICT competencies. Based on the findings, it was concluded that the business educators were applying innovative principles that could lead to improved societal values and that if lectures in other fields follow suit, graduates of tertiary educational institutions would demonstrate appropriate values to reduce the level of moral decadence. Consequently, it was recommended that management of tertiary educational institutions in the area and governments should encourage the business educators and lecturers in other fields of learning to widely apply innovative practices for improved societal values by adequately providing instructional resources and sponsoring them to seminars, conferences and short courses to acquire the relevant skills and competencies.